Loosening the grip - Kinney, Jean
Accessible and comprehensive, Loosening the Grip remains an authoritative source for information about alcohol use and the problems associated with it, while also addressing the relationship between alcohol use and other drug use. This text presents the physical and psychological effects of alcohol alongside the impact of alcohol use on family and society. Special attention is given to addressing the range of responses to alcohol problems: prevention, harm reduction, brief treatment, engagement in treatment and aftercare, and addressing high risk drinking. The book also includes information on alcohol abuse, and alcohol dependence. Along with providing a historical foundation for the discussion of substance use, the book explains the facts about this complex issue in clear, engaging language